Atividade portuária e processos territoriais : uma abordagem urbanística-Grande Vitória (ES) - Fim, Minieli (2015)
The harbor phenomenon in the city can be associated to socio economic relationships, in distinct time and space order, always started by global process. The new information and communication technologies, after 1970, brought multiplication in the number o